The Role of Protein in Nutritional Support and Recovery of Ovarian Cancer Patients: A Narrative Review - Kusuma, Fitriyadi (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Protein intake is essential for maintaining muscle mass, accelerating postoperative recovery, and improving chemotherapy tolerance in ovarian cancer patients. However, few reviews have specifically addressed its impact on prognosis and quality of life. Objective: To review scientific evidence on the effect of protein intake in ovarian cancer patients. Methodology: Literature was searched through PubMed, Scopus, and Google Scholar using keywords such as protein intake, ovarian cancer, muscle mass, fatigue, and quality of life. Studies were selected based on clear methodology and relevance of findings. Results: Protein consumption ?1.5 g/kg body weight/day was associated with increased muscle mass and reduced muscle loss during chemotherapy. Protein supplementation before and after surgery supported gastrointestinal recovery and shortened hospital stay. Adequate protein intake also enhanced immune function and reduced the risk of fatigue and malnutrition. Patients with higher protein intake showed better progression-free survival outcomes. Discussion: Sufficient protein intake supports physical recovery and therapy tolerance in ovarian cancer patients. Nutritional interventions, including protein supplementation, may serve as an important part of comprehensive cancer management. Conclusion: Adequate protein intake plays a significant role in improving clinical outcomes and quality of life for ovarian cancer patients. Nutrition should be personalized as part of cancer care. Recommendation: Nutritional assessment and planning for protein intake should be integrated into the care protocols for ovarian cancer patients, particularly during the perioperative and chemotherapy phases. Collaboration among physicians, dietitians, and oncology teams is essential.